Comparison of Injuring Effects of Vesicant, Irritant, and Nonvesicant Anticancer Drugs on Endothelial Cells - Takaaki Yamada; Nobuaki Egashira; Maiko Imuta; Ayami Bando; Takahisa Yano; Mami Saito; Ryozo Oishi (Elsevier, 2011)
Abstract.: Anticancer drugs are classified as vesicant, irritant, and nonvesicant drugs on the basis of frequency of their vascular disorder. In this study, we compared the injuring effects of three typical anticancer drugs of each class on porcine aorta endothelial cells (PAECs). The concentration inducing 50% cell viability inhibition was lower in the order of vesicant, irritant, and nonvesicant drugs. These results suggest that injuring effects of anticancer drugs on PAECs may be relevant as an indicator of frequency of their vascular disorder, and that this experimental model may be useful for the study of vascular disorder. Keywords:: vascular disorder, anticancer drug, endothelial cell